Telepsychiatry in Australia: A Scoping Review - Luke Sy-Cherng Woon DrPsych; Paul A. Maguire PhD; Rebecca E. Reay PhD; Jeffrey C.L. Looi DrMedSc (SAGE Publishing, 2024)
Telepsychiatry formed part of the Australian mental health response to COVID-19, but relevant reviews pre- and post-pandemic are sparse. This scoping review aimed to map the literature on telepsychiatry in Australia and identify key research priorities. We searched databases (Medline, PubMed, PsycINFO, Scopus, Web of Science, EBSCO Psychology & Behavioral Sciences Collection, Proquest databases, and Cochrane Central Register of Controlled Trials) and reference lists from January 1990 to December 2022. Keywords included telepsychiatry, videoconferencing, telephone consultation, psychiatry, mental health, and Australia. Two reviewers independently screened titles, abstracts, and full texts. We identified 96 publications, one-third of which appeared since 2020. Extracted data included article types, service types, usage levels, outcome measures, perceptions, and research gaps. Most publications were quantitative studies (n = 43) and narrative reports of services (n = 17). Seventy-six papers reported mostly publicly established services. Videoconferencing alone was the most common mode of telepsychiatry. There was increased use over time, with the emergence of metropolitan telepsychiatry during the pandemic. Few papers used validated outcome measures (n = 5) or conducted economic evaluations (n = 4). Content analysis of the papers identified perceptions of patient (and caregiver) benefits, clinical care, service sustainability, and technology capability/capacity. Benefits such as convenience and cost-saving, clinical care issues, and implementation challenges were mentioned. Research gaps in patient perspectives, outcomes, clinical practice, health economics, usage patterns, and technological issues were identified. There is consistent interest in, and growth of, telepsychiatry in Australia. The identified perception themes might serve as a framework for future research on user perspectives and service integration. Other research areas include usage trends, outcome measures, and economic evaluation.